Level of social competence of children enrolled in and not enrolled in kindergarten (comparative study) - Hellal, Sameha Fathy; Al- Sayegh, Yasmin Fathy (Journal of Educational and Psychological Sciences, 2020)
The current research aims to identify the differences between male and female in the study variable (social competence) among children not registered in kindergarten, and to identify the differences between male and female in the study variable (social competence) among children registered in kindergarten, and to identify the differences in competence Sociology among children registered in kindergarten and among children who are not enrolled in kindergarten: The research sample consisted of (60) kindergarten children at the second level. Mental years (5- 6) divided as follows (30 boys and girls are enrolled in kindergarten), (30 boys and girls are not enrolled in kindergarten, and the two researchers used the following tools: Social Proficiency Scale Prepared/ Faten Farouq, IQ scale Dr. Ijilal Sari, the socioeconomic level of Dr. Abdul Aziz Al- Person, the results of this research concluded that there are no statistically significant differences between the average scores of male and female grades among children not registered in kindergarten, and also concluded that there are statistically significant differences between average The grades of children registered in kindergarten and the average grades of Children not enrolled in kindergarten on social competence scale for the benefit of children enrolled in kindergarten.
Keywords: Social Efficienc; Kindergarten Children; Non- Kindergarten Children